2011
DOI: 10.1111/j.1752-0606.2009.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Multicultural Case Conceptualization Ability and Couples Therapy

Abstract: Previous literature on the assessment of multicultural counseling competence has been concerned only with counselors' abilities when working with individual clients. We expanded this line of research by investigating trainees' multicultural case conceptualization ability in the context of working with couples. Despite the fact that trainees self-reported a high level of multicultural competency, trainees were largely inattentive to racial factors in their case conceptualization responses to vignettes involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…As noted previously, researchers have discussed the pitfalls of utilizing self-report measures of MCC (e.g., Constantine & Ladany, 2000;Lantz et al, 2018;Worthington & Dillon, 2011). Common measures of performance-based MCC are supervisor ratings, client ratings, observer ratings (Worthington, Soth-McNett, & Moreno, 2007), and performance on a multicultural case conceptualization ability task (e.g., Guzmán et al, 2013;Ladany et al, 1997;Schomburg & Prieto, 2011). Relatively few studies employ any of the performance-based measures, likely due to their methodologically complex and time-consuming nature.…”
Section: Multimethods Approaches To Measuring Multicultural Competencementioning
confidence: 99%
See 2 more Smart Citations
“…As noted previously, researchers have discussed the pitfalls of utilizing self-report measures of MCC (e.g., Constantine & Ladany, 2000;Lantz et al, 2018;Worthington & Dillon, 2011). Common measures of performance-based MCC are supervisor ratings, client ratings, observer ratings (Worthington, Soth-McNett, & Moreno, 2007), and performance on a multicultural case conceptualization ability task (e.g., Guzmán et al, 2013;Ladany et al, 1997;Schomburg & Prieto, 2011). Relatively few studies employ any of the performance-based measures, likely due to their methodologically complex and time-consuming nature.…”
Section: Multimethods Approaches To Measuring Multicultural Competencementioning
confidence: 99%
“…We used the case conceptualization task in the present study to gain a more accurate representation of participants' MCC as observed through their conceptualization abilities by utilizing a single-participant (rather than dyadic or triadic) design and online data collection. Two recent, similar multimethod examinations were conducted in school counseling (Guzmán et al, 2013) and marriage and family therapy (Schomburg & Prieto, 2011). Schomburg and Prieto (2011) employed the Multicultural Case Conceptualization Ability (MCCA) task (Ladany et al, 1997), adapted for couples therapy, as well as the self-report Multicultural Counseling Knowledge and Awareness Scale (MCKAS; Ponterotto, Gretchen, Utsey, Rieger, & Austin, 2002) with a sample of marriage and family therapy and counseling psychology trainees.…”
Section: Multimethods Approaches To Measuring Multicultural Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Despite broad agreement that attunement to client's sociocultural experience is foundational to good practice (D'Aniello, Nguyen, & Piercy, ), therapists often fail to effectively address societal context, culture, and power (Schomburg & Prieto, ; Williams & Knudson‐Martin, ). We argue that there should be no disconnect between clinical excellence and practice that promotes cultural equity and social transformation (Almeida, Hernández‐Wolfe, & Tubbs, ; St. George & Wulff, ).…”
Section: Equitable Practice Is Good Practicementioning
confidence: 99%
“…Another limitation is due to the self‐report nature of the survey. Research typically shows a weak relationship between a person's perception of what they do and their actual behavior (Schomburg Schomburg & Preto, ). In this case, it is not possible to know if the therapists’ answers reflect what would actually occur in session with a given client.…”
Section: Future Research and Limitationsmentioning
confidence: 99%